Waist circumference is correlated with poorer cognition in elderly type 2 diabetes women. Issue 8 (2nd May 2016) - West, Rebecca K.; Ravona‐Springer, Ramit; Heymann, Anthony; Schmeidler, James; Leroith, Derek; Koifman, Keren; D'Arcy, Ryan C.N.; Song, Xiaowei; Guerrero‐Berroa, Elizabeth; Preiss, Rachel; Hoffman, Hadas; Sano, Mary; et al.
Abstract: Introduction: Waist circumference is associated with type 2 diabetes (T2D) and cognition, yet the relationship between waist circumference and cognition in individuals with T2D is not well understood. Methods: We studied the relationship of waist circumference with five cognitive outcomes (executive functioning, language/semantic categorization, attention/working memory, episodic memory, and an overall cognition measure) in 845 cognitively normal elderly with type 2 diabetes (T2D). Results: In women, waist circumference was correlated with significantly lower language and/or semantic categorization performance ( P < .0001), executive functioning ( P = .026), and overall cognition ( P = .003) after controlling for age, education, BMI, and cardiovascular, diabetes‐related, APOE ε4, and inflammatory potential confounders. Attention/working memory ( P = .532) and episodic memory ( P = .144) were not associated with waist circumference. These correlations were not found in men. Discussion: These results suggest that central adiposity in elderly women with T2D may increase their risk for dementia.